2015
DOI: 10.2146/ajhp140134
|View full text |Cite
|
Sign up to set email alerts
|

Safe and effective use of eculizumab in the treatment of severe Shiga toxinEscherichia coli-associated hemolytic uremic syndrome

Abstract: An 18-year-old man who developed severe HUS due to STEC O121 and was unresponsive to traditional supportive therapies was successfully treated with eculizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…On the other hand, enhanced plasmin generation and fibrinolysis, as expected in the Cpb2 −/− mice and supported by the higher levels of D‐dimer, should lead to a decreased clot burden and a beneficial effect in these mice, rather than increased disease susceptibility; thus, fibrin is probably not a key substrate in this model. Eculizumab is an anti‐human C5 antibody with an equivalent mode of action to the anti‐mouse C5 antibody used in our studies and has been shown to have beneficial effects in Shiga toxin‐producing E. coli infections, especially when administered early .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, enhanced plasmin generation and fibrinolysis, as expected in the Cpb2 −/− mice and supported by the higher levels of D‐dimer, should lead to a decreased clot burden and a beneficial effect in these mice, rather than increased disease susceptibility; thus, fibrin is probably not a key substrate in this model. Eculizumab is an anti‐human C5 antibody with an equivalent mode of action to the anti‐mouse C5 antibody used in our studies and has been shown to have beneficial effects in Shiga toxin‐producing E. coli infections, especially when administered early .…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados de este tratamiento en niños con compromiso neurológico severo por SHU+D aún son inciertos, por lo que es necesario evaluar crí-ticamente los resultados de los estudios que se llevan a cabo en la actualidad antes de recomendar su uso [7][8][9][10]22 .…”
Section: Discussionunclassified
“…Todos deben detectarse y tratarse precozmente incluyendo diálisis en falla renal aguda. No obstante, la plasmaféresis y el uso de antagonistas de proteínas del complemento podrían ser alternativas frente al compromiso severo del SNC [7][8][9][10] .…”
Section: Introductionunclassified
“…Purified C1 inhibitor is indicated for the treatment of hereditary or acquired C1 inhibitor deficiency. A humanized monoclonal antibody, eculizumab, has been used for several years to treat paroxysmal nocturnal hemoglobinuria (PNH) and more recently has been used successfully in several cases of shiga-toxin associated hemolytic uremic syndrome (Delmas, et al, 2014, Dinh, et al, 2015, Lapeyraque, et al, 2011). Other products in various stages of development include: antibodies or fragments of antibodies directed against C5, factor D, C1s or MASP-2; small molecules that block factor D, C5aR or C3 or soluble complement inhibitors of complement (CR1 or fragments of FH).…”
Section: Introductionmentioning
confidence: 99%